Peran Gizi Kerja Dalam Meningkatkan Produktivitas Dan Kinerja Karyawan: Tinjauan Literatur - Fitri Handayani; Fithri Handayani Lubis (STIKES Columbia Asia Medan, 2025)
This study aims to examine the relationship between occupational nutrition and employee productivity through a systematic literature review. The background of this research lies in the increasing attention to workplace health and the growing evidence that nutritional status can influence physical performance, cognitive function, and work outcomes. A total of 74 articles were initially identified from databases such as PubMed, ScienceDirect, Google Scholar, and Garuda, of which 12 met the inclusion criteria and were analyzed further. The findings indicate that adequate intake of macronutrients and micronutrients—particularly iron, protein, and B vitamins—correlates positively with productivity levels. Interventions such as nutritional education, iron supplementation, and structured meal programs at the workplace showed measurable effects in reducing absenteeism and fatigue while improving concentration and efficiency. The study concludes that occupational nutrition plays a vital role in supporting workforce performance and suggests its integration into workplace health policies. Theoretical and practical implications are discussed, along with recommendations for future research